Evaluating recall of key safety messages, and attitudes and perceptions of a patient safety initiative at a pediatric hospital - Deepika Sriram; Carol Cooke; Régis Vaillancourt; Gilda Villarreal; Annie Pouliot; Nanette Labelle; Tracy Wrong (The Beryl Institute, 2016)
Involving inpatients in their safety and well-being is becoming increasingly common. Interventions have been developed to encourage patients to be active in their own safety, but published evaluations are scarce. The Patient Safety Ambassador (PSA) program was developed to increase patient and parent/guardian engagement and knowledge in patient safety. This study aimed to determine recall ability of key safety messages and explore attitudes and perceptions towards the PSA program, hence obtaining feedback for program improvements. Participants were pediatric inpatients and parents of inpatients. Face-to-face semi-structured interviews were conducted. Cued and non-cued recall ability was determined using questions with and without specific cues, while attitudes and perceptions were explored using open-ended questions regarding patient safety. QSR NVivo 10 software was used to analyze interviews for recall ability and major themes. 95% of parents could remember all safety messages with cues, but could only remember one (35%) or two (32.5%) messages without cues. Inpatient participants could remember up to 4 messages with cues, no messages without cues, and, unlike parents, were unable to discuss their attitudes and perceptions towards safety. Five major themes emerged from analysis of interviews with parents: the importance of medication knowledge, parental involvement in care, having trust in healthcare team, asking questions, and advocacy. Use of cues appears beneficial in facilitating recall of safety messages. Parents had varied attitudes and perceptions to safety. Future research can explore methods to engage pediatric inpatients, integrate cues to increase recall, and examine resulting behavioural changes.